Comparative evaluation of human chorion membrane and platelet-rich fibrin membrane with coronally advanced flap in treatment of Miller's class I and II recession defects: A randomized controlled study - Shivani Ashwinikumar Dandekar; Neeraj Chandrahas Deshpande; Deepak Harishchandra Dave (Wolters Kluwer Medknow Publications, 2019)
Background: Root coverage procedures have gained much popularity in recent years, due to increasing esthetic demands of patients. Coronally advanced flap (CAF) is a predictable technique for treating gingival recessions. Platelet-rich fibrin (PRF), an autologous platelet concentrate, has properties to enhance soft-tissue wound healing. A current method in dentistry is the use of human chorion membrane, a placental derivative, having biologic properties that help in healing and regeneration. Thus, the aim of the study was evaluation and comparison of the efficacy of chorion membrane and PRF membrane in the treatment of Miller's Class I and Class II recession defects. Materials and Methods: This was a randomized controlled clinical study. Totally 30 sites with Miller's Class I and Class II recession were taken and randomly allocated to chorion membrane (test) PRF membrane (control) group. The clinical parameters recorded were clinical attachment level (CAL), recession height (REC-HT), recession width (REC-WD), width of keratinized gingiva (WKG) and gingival tissue thickness (GTH). Results: Significant differences were seen from baseline to 6 months in test group regarding gain in CAL (P < 0.001), reduction in REC-HT (P < 0.001), decrease in REC-WD (P = 0.02), increase in WKG (P < 0.001), and increase in GTH (P < 0.001). In the control group also, significant difference was noted at the end of 6 months i regarding gain in CAL (P < 0.001), reduction in REC-HT (P < 0.001), decrease in REC-WD (P = 0.029), increase in WKG (P < 0.001), and increase in GTH (P < 0.001). Intergroup analysis showed significant differences between test and control groups at the end of 6 months, with CAL, REC-HT, WKG, and GTH showing statistically significant differences with P = 0.002, 0.001, 0.001, and 0.026, respectively. No significant difference was seen regarding REC-WD (P = 0.39). Conclusions: Both are effective materials in root coverage, but chorion membrane showed better and more stable results at the end of 6 months as compared to PRF membrane in treating gingival recession.